EKSPERIMENTASI MODEL PEMBELAJARAN TIPE NUMBERED HEAD TOGETHER (NHT) DAN THINK-PAIR-SHARE (TPS) DITINJAU DARI GAYA BELAJAR SISWA PADA POKOK BAHASAN RELASI DAN FUNGSI KELAS VIIISMP NEGERI SE-KABUPATEN PACITAN TAHUN PELAJARAN 2015/2016 - Heritin, Anisak; Budiyono, Budiyono; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2016)
Abstrak: The objective of the research was to know in each category learning style (visual, auditorial, and kinesthetic) which one providing better mathematics learning achievement, NHT, TPS, or direct learning model. This research was a quasi-experimental and designed in a 33 factorial design. The population of research was students in grade VIII of Junior High Schools of Pacitan Regency in this academic year of 2015/2016. The sample was taken by stratified cluster random sampling. Results of this research were concluded as follows: (1) in NHT and TPS model, visual, auditorial, and kinesthetic learning style have similar result of learning achievement, (2) in direct learning model, students of auditorial learning style have better than learning achievement kinesthetic learning style, visual learning style have learning achievement as good as auditorial learning style, students of visual learning style have learning achievement as good as kinesthetic learning style, (3) in visual learning style, NHT have learning achievement as good as TPS, NHT and TPS have better than learning achievement direct learning model, (4) in auditorial learning style, NHT have learning achievement as good as TPS, NHT and TPS have learning achievement as good as direct learning model, and (5) in kinesthetic learning style, NHT have learning achievement as good as TPS, TPS have better learning achievement than direct learning model, NHT have learning achievement as good as direct learning model.Keyword: NHT, TPS, Direct learning Model and Learning StyleÂ